Support programs for parents of children with disabilities - Šćepanović, Marinela N (Sinteze - časopis za pedagoške nauke , književnost i kulturu, 2017)
Paper deals importance and position of upbringing children with disabilities, and it gives review of ten efficient, evidence-based, support programs created for parents of children with disabilities, which are used globally. Contemporary concept of children upbringing at all means interaction parent and child in a process of upbringing and participation of child in its own development. In those setting, parents of children with disabilities need strong support regarding strengthening parental capacities and building special sills, because their children have less of capacities. There are no support programs for parents of children with disabilities in Serbia. Evidence-based and proven support programs for families and parents have to be provided, promoted and offered as constantly available support for parents and children with disabilities within the comprehensive and complex process of upbringing.